2016
DOI: 10.1177/0007650316680060
|View full text |Cite
|
Sign up to set email alerts
|

Creating Community-Inclusive Organizations: Managerial Accountability Framework

Abstract: Based on a community psychology perspective, this qualitative study explores the community inclusion effort of one of the largest pulp and paper companies in the world. Extending the literature on workforce diversity/inclusion, we present the community inclusive organizational framework, which signifies the dynamics of community inclusiveness of organizations highlighting key managerial accountabilities (i.e., cultural, collective, relational and structural accountabilities) based upon the community psychology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Here, "conflict" refers to community opposition and resistance to the extractive projects on their territory, not to be confused with other contexts of conflict, such as armed civil war. Stakeholder engagement theorists would be well advised to consider the limits of stakeholder engagement for resolving conflicts, improving relations and contributing to development, as proposed by business ethics authors (Calvano 2008;Stückelberger 2009;Newenham-Kahindi 2011;Muthuri et al 2012;Fujimoto et al 2016). External actors can deepen internal community divisions, which can be interpreted as a strategic advantage for the company in terms of ruling by division.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, "conflict" refers to community opposition and resistance to the extractive projects on their territory, not to be confused with other contexts of conflict, such as armed civil war. Stakeholder engagement theorists would be well advised to consider the limits of stakeholder engagement for resolving conflicts, improving relations and contributing to development, as proposed by business ethics authors (Calvano 2008;Stückelberger 2009;Newenham-Kahindi 2011;Muthuri et al 2012;Fujimoto et al 2016). External actors can deepen internal community divisions, which can be interpreted as a strategic advantage for the company in terms of ruling by division.…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholder engagement and community participation are largely seen as the appropriate approach to resolving such conflicts (Zandavillet and Anderson 2009;Newenham-Kahindi 2011;ICMM 2015;Fujimoto et al 2016;IDB 2017). Numerous manuals, toolkits and guidance documents are produced by organizations such as the International Council on Mining and Metals (ICMM 2015), the Inter-American Development Bank (IDB 2017), the World Bank's International Finance Corporation (IFC 2007), Herbertson et al (2009) and Business for Social Responsibility (BSR).…”
Section: Community Engagement Conceptualizedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the aspect missing from the inclusion literature is an integrative workplace model where inclusion of the poor is empowered through the involvement of multiple parties inside and outside of workplaces. With little institutional support and limited access to valuable resource networks for the poor in developing countries, the poor face multiple social, economic and psychological challenges inside and outside of work domains that may require an outside-in and inside-out empowering relationships to transform their lives (Fujimoto et al , 2019). Notably, previous research has reported norms of collectivity as a source of daily survival for the poor (Moser, 1996).…”
Section: Inclusive Workplace For the Poormentioning
confidence: 99%
“…A broad definition of inclusion, according to Ferdman (2017, p. 235) indicates: "In inclusive organizations and societies, people of all identities and many styles can be fully themselves while also contributing to the larger collective, as valued and full members." In addition, the existing literature commonly defines inclusion as "minority members' insider status, belongingness, full contribution, engagement, voice, and participation in the organizational decision-making process, as well as the means to draw out minority members' unique perspectives and to integrate differences within a workplace" (Fujimoto, Azmat, & Subramaniam, 2019). According to Shore et al (2018), inclusion involves "equal opportunity for members of socially marginalized groups to participate and contribute while concurrently providing opportunities for members of non-marginalized groups, and to support employees in their efforts to be fully engaged at all levels of the organization and to be authentically themselves" (p.177).…”
Section: Introductionmentioning
confidence: 99%